2017
DOI: 10.7554/elife.27081
|View full text |Cite
|
Sign up to set email alerts
|

Polyglycerol-opioid conjugate produces analgesia devoid of side effects

Abstract: Novel painkillers are urgently needed. The activation of opioid receptors in peripheral inflamed tissue can reduce pain without central adverse effects such as sedation, apnoea, or addiction. Here, we use an unprecedented strategy and report the synthesis and analgesic efficacy of the standard opioid morphine covalently attached to hyperbranched polyglycerol (PG-M) by a cleavable linker. With its high-molecular weight and hydrophilicity, this conjugate is designed to selectively release morphine in injured tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 55 publications
0
34
0
Order By: Relevance
“…HEK293 cells stably expressing rat MOR were cultured in flasks with a growth area of 175 cm². Cells were washed twice with ice-cold assay buffer (Trizma® Preset Crystals, 50 mM, pH 7.4) (Sigma-Aldrich), then scratched from the culture flask in 10 ml ice cold assay buffer, homogenized and centrifuged twice at 42,000 g for 20 min at 4 °C as described previously 7 , 19 , 20 . Protein concentration was determined according to the Bradford method 21 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HEK293 cells stably expressing rat MOR were cultured in flasks with a growth area of 175 cm². Cells were washed twice with ice-cold assay buffer (Trizma® Preset Crystals, 50 mM, pH 7.4) (Sigma-Aldrich), then scratched from the culture flask in 10 ml ice cold assay buffer, homogenized and centrifuged twice at 42,000 g for 20 min at 4 °C as described previously 7 , 19 , 20 . Protein concentration was determined according to the Bradford method 21 .…”
Section: Methodsmentioning
confidence: 99%
“…A protein amount of 80–100 µg was incubated with 4 nM [ 3 H]-DAMGO (50 Ci/mmol) and FF3 dissolved in 50 mM assay buffer at pH 6.5 or 7.4 for 90 min at room temperature. Nonspecific binding was determined by the addition of 10 µM NLX 20 . Filters were soaked in 0.1% polyethyleneimine solution before use.…”
Section: Methodsmentioning
confidence: 99%
“… 33 Targeting peripheral opioid receptors in damaged tissue avoids adverse opioid effects in the brain or gut, as well as detrimental side effects of NSAIDs, as demonstrated in animal models and humans with acute and chronic pain. 11 , 29 , 32 , 33 , 37 , 41 Moreover, pharmacological, genetic, and clinical studies have shown that a large proportion of opioid analgesia is mediated by peripheral opioid receptors 10 , 15 , 39 and that such receptors can confer significant anti-inflammatory effects. 34 …”
Section: Introductionmentioning
confidence: 99%
“…[39,42] The paw pressure threshold (cut-off at 250 g) required to elicit paw withdrawal was determined by averaging three consecutive trials separated by 15-s intervals. [39,42] The paw pressure threshold (cut-off at 250 g) required to elicit paw withdrawal was determined by averaging three consecutive trials separated by 15-s intervals.…”
Section: Methodsmentioning
confidence: 99%
“…In Figure 4 the release of U50 from either of the four nanocarrier architectures or as a mesylate salt is depicted. [41][42][43] Without any carrier (black and blue curves, Figure 5, left and right) there was no difference between pH 7.4 and 5.5. Compared to that, the release from CMS-A only seemed to feature a weak retention effect, as the blue curve (Figure 4, right) did not differ from the black one very strongly and the error bars partially overlapped.…”
Section: Release Kinetics Of U50 From Different Nanocarriersmentioning
confidence: 97%